Reputasi Pemerintah Provinsi Lampung Setelah Unggahan Bima di Laman Sosial Media Tik Tok - Amar Farhan, Muhammad (Journal of Comprehensive Science, 2023)
Reputation is an important component for the survival of a company. Not only required by companies, reputation is also important for government agencies, both executive and legislative. The higher the quality of reputation owned by government agencies indicates the good system run by the government. This is similar to what happened to the government of Lampung Province. Criticisms and suggestions submitted by its residents indicate the necessity of holding an evaluation regarding community complaints. This research was prepared using qualitative methods. Sources obtained based on circulating news and developed using reputation theory. The results of this study suggest that after Tiktoker Bima uploaded a video which revealed the low quality of infrastructure in Lampung, many Lampung residents protested to the local government. However, the Lampung government is considered to be less open and reactive towards criticism and suggestions from its people.